The Relationship Of The Construction Cost Index To Human Development Index In West Nusa Tenggara - Az-Zahra, Al Farrah; Robbaniyyah, Nuzla Af'idatur (JSN : Jurnal Sains Natural, 2025)
The Construction Cost Index (CCI) is an index that describes how expensive it is to build a building, the higher the index, the greater the cost. Meanwhile, the Human Development Index (HDI) is an index used to measure the quality of life of the people in a region, the higher the value, the better the quality of life. It is important to know how the pattern and dynamics of the relationship between CCI and HDI. Therefore, this paper aims to determine the relationship between CCI and HDI in West Nusa Tenggara Province. The data taken is secondary data derived from Central Bureau of Statistics. First, define the hypothesis between CCI and HDI, where CCI and HDI are assumed to have a negative relationship, which means that the higher HDI, the lower CCI, and vice versa, the lower HDI, the higher CCI.The average CCI in West Nusa Tenggara falls into the high category, as does the HDI. After that, compare the CCI and HDI values in each region with the previous region, where Makassar City is used as the initial comparison for the CCI category, as it is the region closest to or equal to the national average index. As a result, most regions show the hypothesized negative relationship. out of 10 regions, only Sumbawa District, West Sumbawa District, and Bima District show a negative relationship.